Association of Circulating Apolipoprotein AI Levels in Patients With Alzheimer's Disease: A Systematic Review and Meta-Analysis - Tong, Jun-hui; Gong, Shi-qiang; Zhang, Yan-song; Dong, Jian-ru; Zhong, Xin; Wei, Min-jie; Liu, Ming-yan (Frontiers in Aging Neuroscience, 2022)
With the development of medicine, our research on Alzheimer's disease (AD) has been further deepened, but the mechanism of its occurrence and development has not been fully revealed, and there is currently no effective treatment method. Several studies have shown that apolipoprotein AI (ApoA-I) can affect the occurrence and development of Alzheimer's disease by binding to Aβ. However, the association between circulating levels of ApoA-I and AD remains controversial. We conducted a meta-analysis of 18 studies published between 1992 and 2017 to determine whether the ApoA-I levels in the blood and cerebrospinal fluid (CSF) are abnormal in AD. Literatures were searched in PubMed, EMBASE and Web of Science databases without language limitations.A pooled subject sample including 1,077 AD patients and 1,271 healthy controls (HCs) was available to assess circulating ApoA-I levels; 747 AD patients and 680 HCs were included for ApoA-I levels in serum; 246 AD patients and 456 HCs were included for ApoA-I levels in plasma; 201 AD patients and 447 HCs were included for ApoA-I levels in CSF. It was found that serum and plasma levels of ApoA-I were significantly reduced in AD patients compared with HCs ((standardized mean difference [SMD] = -1.16; 95% confidence interval [CI] [-1.72, -0.59]; P = 0.000) and (SMD = -1.13; 95% CI [-2.05, -0.21]; P = 0.016)). There was statistically non-significant for ApoA-I level in CSF between AD and HCs, whereas a increased tendency were detected (SMD = 0.20; 95% CI [-0.16, 0.56]; P = 0.273). In addition, when we analyzed the ApoA-I levels of serum and plasma together, the circulating ApoA-I levels in AD patients was significantly lower (SMD = -1.15; 95% CI [-1.63, -0.66]; P = 0.000). These results indicate that ApoA-I deficiency may be a risk factor of AD, and ApoA-I has the potential to serve as a biomarker for AD and provide experimental evidence for early diagnosis and treatment of AD.